PENGARUH WAKTU REAKSI TERHADAP KARAKTERISTIK PENCAIRAN BATUBARA BANKO SELATAN - Artanto, Yuli; Yusnitati, Yusnitati (Jurnal Energi dan Lingkungan (Enerlink), 2006)
Investigation of Limonite for catalyst on South Banko coal liquefaction werecarried out under standard condition which has developed by BPPT.Limonite Soroako is a natural mineral that found at Nickel Mining onSoroako, South Sulawesi. Four samples of limonite was examined using 5Lautoclave at our coal liquefaction laboratory in order to investigate theisactivities to produce high distillate yield at standard condition (450oC, 9MPacold H2). The results showed that limonite SYY-E-MY gave a higher distillateyield than those of other limonite (difference about 10-30%daf coal or%bkta). Further investigations were conducted to compare with othercatalysts: synthetic g –FeOOH and pyrite (FeS2). Again, the activity of limonitS99-E-MY was still superior compared to those of synthetic and pyritecatalysts. The yield difference was about 10-16%daf coal or %bkta).Experiment revealed that the factor of FeOOH critically affected the coalliquefaction reaction to improve the distillate yield and to reduce CLB yield.Besides, the representative of Co metal in the limonite (≥5-10 %bk) couldgive synergism effect with FeOOH to improve the activity of limonite.